Phytochemical composition, anti-fungal activity of Mucuna pruriens (L.) DC. (Fabaceae) seed extract and acute toxicity testing of formulated herbal ointment (2023)
The growing resistance to conventional dandruff remedies has led to the search for newer and affordable treatments from African medicinal plants. This study evaluates the anti-fungal activity of methanol extract of the seed of Mucuna pruriens L. (DC.) Fabaceae (MP) against Malassezia furfur and Malassezia globosa which have been implicated in dandruff etiology. The MP seed sample was collected from Orba, Enugu State, dried, and pulverized. Macroscopic, microscopic, and phytochemical evaluations of the seed were done. Defatting was done with n-hexane extract and cold maceration with methanol for 72 h (ME extract). The anti-fungal activity of the extracts was determined using the agar dilution method with ketoconazole as standard. Two samples of ointment containing 5% and 10% MP seed methanol extract were prepared with an emulsifying base using a fusion technique. An acute skin toxicity test was carried out by applying the formulation to the skin of albino rats and observations were made. Results: Quantitative phytochemical analysis of secondary metabolites in the MP seed gave: phenolic content (8.3%), alkaloids (0.02%), flavonoids (0.2%), saponins (0.4%), tannins (0.09%). The ME extract inhibited growths of Malassezia furfur (MIC 3 mg/mL) and Malassezia globosa (MIC 2 mg/mL). The 5% and 10% samples of the herbal ointment MPO showed no toxicity or irritancy on the animals. Conclusion: Methanol extract of Mucuna pruriens possess antifungal activity against Malassezia furfur and Malassezia globosa and its ointment appears non-toxic.